A Decade of Deadlock. The EU’s Shipwreck on Palestine Embodies the EU’s Blockade Problem/ How the G7 Can Effectively Back Africa’s Twin Goal of Energy Access and Transition - (:unkn) unknown (My University, 2024)
Αυτή η πτυχιακή εργασία έχει στο επίκεντρο της την μετάφραση και τον σχολιασμό της μετάφρασης δυο άρθρων. Πρόκειται για άρθρα κοινωνικοπολιτικού και οικονομικού περιεχομένου, το «A Decade of Deadlock. The EU’s Shipwreck on Palestine Embodies the EU’s Blockade Problem» και το «How the G7 Can Effectively Back Africa’s Twin Goal of Energy Access and Transition». Έπειτα από τη μετάφραση των άρθρων αυτών, επεξηγείται η μεταφραστική διαδικασία και ορίζεται η προσέγγιση που ακολουθήθηκε. Επιπλέον, αναλύεται λεπτομερώς η ειδική ορολογία και αναγνωρίζονται σε πρώτη φάση οι μεταφραστικές δυσκολίες. Έπειτα, οι δυσκολίες αυτές κατηγοριοποιούνται σε ομάδες, ενώ αργότερα επεξηγείται η επιλογή όρου, δηλαδή η τρόπος αντιμετώπισης που θεωρήθηκε δέων για κάθε περίπτωση. Μεταφραστικές δυσκολίες μπορούν να θεωρηθούν και πρακτικά εμπόδια τα οποία μπορεί να συναντήσει κάποιος στην μεταφορά των κειμένων-πηγή στα κείμενα-στόχο.

This thesis focuses on the translation and commentary of two articles. These are socio-political and economic articles, "A decade of deadlock. The EU's shipwreck on Palestine embodies the EU's blockade problem" and "How the G7 can effectively support Africa's twin goals of energy access and transition". After translating these articles, the translation process is explained and the approach taken is defined. In addition, specific terminology is analysed in detail and translation difficulties are identified. These difficulties are then grouped and the choice of terminology, i.e. the approach considered appropriate in each case, is explained. Translation difficulties can also be seen as practical obstacles that may be encountered when transferring source texts to target texts.
Η Αδιαφορία της ΕΕ για την Παλαιστίνη – Το Αιματηρό Δεκαετές Πρόβλημα./Πώς η G7 Μπορεί να Υποστηρίξει Αποτελεσματικά τον Διπλό Στόχο της Αφρικής για Ενεργειακή Πρόσβαση και Μετάβαση.
Keywords: Παλαιστινιακό, G7, Ευρωπαϊκή Ένωση.; Israel-Palestine agenda, G7, European Union.